Experimental Investigation into Natural Convection Heat Transfer inside Triangular Enclosure with Internal Hot Cylinder - Mohammed, Akeel Abdullah; Mohammed, Ansam Adil; Channapattanac, Shylesha V. (Al-Nahrain Journal for Engineering Sciences, 2023)
Natural convection air heat transfer and fluid movement currents around a hot circular cylinder inside an inclined triangular enclosure has been analyzed experimentally. Three different sizes of an enclosure with a long side of 20, 25, and 30 cm, the thickness of 1 mm, and depth of 50 cm were used in the present work to give three radius ratios. The effect of Rayleigh number, radius ratio, the rotation angle of triangle enclosure, and the inclination angle of the apparatus with horizontal axis ? on the heat transfer process was investigated. The ranges of these parameters were: Rayleigh number from 5×106 to 2.5×108, radius ratio (0.345, 0.455, and 0.618), rotation angle (0o, 45o, and 90o), and inclination angle (0o, 45o and 90o). The results show that the heat transfer rates increase with increase in Rayleigh number and as the rotation angle of enclosure is changed from 0o to 90o. Moreover, the heat transfer rate increases linearly with Rayleigh number at higher radius at rotation angle 0o, 90o only. While, it increases slightly with Rayleigh number at rotation angle 45o. Additionally, the higher heat transfer rates occur at vertical position of enclosure inclination angle 90o and rotation angle 0o (the base of triangle at the bottom) and it decreases as inclination angle deviates from 90o to 0o. This behavior is reverse completely at higher radius ratio 0.618. Empirical correlations for the average Nusselt number has been found to depend on Rayleigh number., radius ratio, rotation angle and inclination angle.